KAJIAN EROSI LAHAN PADA DAS DAWAS KABUPATEN MUSI BANYUASIN - SUMATERA SELATAN - Msy Efrodina Ribka Alie (Jurnal Teknik Sipil dan Lingkungan, 2015)
The purpose of this research is to know how great the average erosion has done in a year, the wide field per hectare that happened in watershed Dawas. Together with increasing public requisites of the population people consequence. The field requisites for increasing agriculture and the advantage field in roundabout watershead Dawas that more increase. Calculation of the magnitude of this erosion using Universal Soil Loss Equation (USLE) method. This research began with analyze in several factors which has become attect erosion as rain fall (R), the kind of soil to secure of the soil erodibility (K), to figure out of the sloping valley factors (LS), and the field processing and the plant processing (CP). Based on the analysis has done with Universal Soil Loss Equation (USLE) method, the total average erotion in watershed Â Dawas area is 25,6826 ton/ha/yr with the clasification of the light erotion. Key Words : DAS, Erosion Danger,rainfall